Catalyst system, method for preparing ultra-high molecular weight polyethylene and application

By using a catalyst system containing solid catalyst components and organoaluminum compounds in the industrial production of ultra-high molecular weight polyethylene, the problem of difficulty in maintaining low temperature polymerization is solved, and the stable production of ultra-high molecular weight polyethylene under high temperature conditions is achieved, and the molecular weight uniformity and polymerization activity of the product are improved.

CN119798497APending Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411389558.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-09-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the industrial production of ultra-high molecular weight polyethylene, it is difficult to maintain a low polymerization temperature, resulting in unstable molecular weight of the polymerization product and the polymerization activity of the catalyst system is difficult to maintain for a long time, affecting product quality.

Method used

A catalyst system is provided, which includes solid catalyst components and an organoaluminum compound, which can catalyze ethylene polymerization under high temperature (70-90°C), reduce the influence of temperature changes on the molecular weight of ultra-high molecular weight polyethylene, and maintain the polymerization activity of the catalyst system.

Benefits of technology

This catalyst system can stabilize the production of ultra-high molecular weight polyethylene under high temperature conditions, reduce the impact of temperature fluctuations on molecular weight, improve the molecular weight uniformity and polymerization activity of the product, and improve product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798497A_ABST
    Figure CN119798497A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst system, a method for preparing ultra-high molecular weight polyethylene and application, and belongs to the technical field of olefin polymerization. The catalyst system comprises a solid catalyst component and an organic aluminum compound; the solid catalyst component comprises a titanium element, a magnesium element, an alkoxy compound, a phosphorus element and halogen; the organic aluminum compound contains organic aluminum I and organic aluminum II, the solid catalyst component does not contain a silicon dioxide carrier, the organic aluminum I has a general formula of AlR1R2R3, and in the formula, R1, R2 and R3 are the same or different and are respectively and independently C6-C20 alkyl; and the organic aluminum II has a general formula of AlR '1R' 2R '3, and R' 1, R '2 and R' 3 are the same or different from each other and are independently C1-C5 alkyl groups. Compared with a catalyst system commonly used in industry, the catalyst system provided by the invention can reduce the influence of temperature on the molecular weight of the produced ultra-high molecular weight polyethylene and / or maintain the polymerization activity of the catalyst system for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of olefin polymerization catalysts, and in particular relates to a catalyst system for preparing polyethylene, a method for preparing ultra-high molecular weight polyethylene using the catalyst system, and an application of the catalyst system for preparing polyethylene. Background Art

[0002] Ultra-High Molecular Weight Polyethylene (Ultra-High Molecular Weight Polyethylene) refers to a linear structure thermoplastic engineering plastic with a relative molecular mass of more than 1.5 million. It has many excellent properties that other engineering plastics cannot match, such as high strength, high modulus, low temperature resistance, wear resistance, chemical corrosion resistance, anti-adhesion, self-lubrication and excellent insulation. It can be used in textile, papermaking, packaging, chemical industry, military industry, medical and aerospace fields.

[0003] Ultra-high molecular weight polyethylene is particularly suitable for the production of parts that require higher physical properties, such as transmission gears, artificial joints, etc. In addition, its high modulus and high tensile strength can also be used to produce high-strength fibers. Ultra-high molecular weight polyethylene products are increasingly attracting people's attention and attention, and ultra-high molecular weight polyethylene resins with larger relative molecular weight are widely in demand due to their higher strength, higher modulus and better wear resistance.

[0004] At present, the Ziegler-Natta catalyst system is mainly used to produce ultra-high molecular weight polyethylene through ethylene polymerization reaction, so the performance of the polymer product mainly depends on the type and structure of the catalyst. The Ziegler-Natta catalyst system consists of two parts: a solid catalyst and a co-catalyst. The solid catalyst mostly uses a catalyst component with magnesium, titanium and halogen as the basic components, and the co-catalyst is generally triethylaluminum.

[0005] With the progress of ultra-high molecular weight polyethylene synthesis technology, its synthesis process also tends to develop in a specialized way. For example, in order to improve the wear resistance of the material or the characteristics of higher strength and modulus, it is necessary to use ultra-high molecular weight polyethylene resin with a larger molecular weight. It is well known that the molecular weight of polyethylene decreases with the increase of polymerization temperature. Therefore, the temperature is generally controlled at 50-70°C when the Ziegler-Natta catalyst is used to produce ultra-high molecular weight polyethylene in industry. A lower polymerization temperature can make the polymer have a higher molecular weight, but at the same time reduce the polymerization activity; for current industrial production conditions, polymer products with higher molecular weight are generally obtained at a lower polymerization temperature; however, for industrial production, due to the intense heat release of ethylene polymerization, it is very difficult to maintain a lower polymerization temperature in the industrial production of ultra-high molecular weight polyethylene, and there are high requirements for the heat removal capacity of the reactor, which requires high cost investment and high energy consumption, which is not conducive to the rational use of resources and cannot meet the requirements of green enterprises. In the industrial production of ultra-high molecular weight polyethylene, it would be beneficial if a catalyst system and method for producing ultra-high molecular weight polyethylene under high temperature (70-90°C) conditions could be provided to reduce the influence of temperature on the molecular weight of the produced ultra-high molecular weight polyethylene and / or maintain the polymerization activity of the catalyst system for a long time. Lowering the temperature's effect on the molecular weight of the polymerization product can make the molecular weight of the polyethylene polymer more stable, which is beneficial to improving the quality of ultra-high molecular weight polyethylene products.

[0006] The present application provides a catalyst system and a polymerization method, which can reduce the effect of temperature on the molecular weight of the produced ultra-high molecular weight polyethylene and / or maintain the polymerization activity of the catalyst system for a long time. Summary of the invention

[0007] The purpose of the present invention is to provide a catalyst system for preparing polyethylene, especially ultra-high molecular weight polyethylene, a method for preparing polyethylene, especially ultra-high molecular weight polyethylene, and its application in ethylene polymerization. When the catalyst system of the present invention catalyzes ethylene polymerization to produce polyethylene, especially ultra-high molecular weight polyethylene under high temperature (70-90° C.), compared with the catalyst system commonly used in industry, it can reduce the influence of temperature change on the molecular weight of ultra-high molecular weight polyethylene and / or maintain the polymerization activity of the catalyst system for a long time.

[0008] In the first aspect of the present invention, a catalyst system is provided, the catalyst system comprising a solid catalyst component and an organoaluminum compound; the solid catalyst component comprises titanium, magnesium, an alkoxy compound, phosphorus and a halogen; and the organoaluminum compound comprises organoaluminum I and organoaluminum II, wherein the solid catalyst component does not comprise a silica carrier, wherein the organoaluminum I has a general formula A1R1R2R3, wherein R1, R2 and R3 are the same or different and are independently C6 to C 20and wherein the organoaluminum II has the general formula AlR'1R'2R'3, wherein R'1, R'2 and R'3 are the same or different from each other and are each independently a C1 to C5 hydrocarbon group.

[0009] In the second aspect of the present invention, there is provided an application of the catalyst system of the present application in an ethylene polymerization reaction, preferably an application in an ethylene polymerization reaction to reduce the effect of temperature change on the molecular weight of ultra-high molecular weight polyethylene.

[0010] In the third aspect of the present invention, a method for preparing ultra-high molecular weight polyethylene is provided, the method comprising polymerizing ethylene in an inert solvent in the presence of the catalyst system of the present application to produce ultra-high molecular weight polyethylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The activity curves of different catalyst systems over time are shown. DETAILED DESCRIPTION

[0012] The present invention provides a catalyst system, which comprises a solid catalyst component and an organoaluminum compound; the solid catalyst component comprises titanium, magnesium, an alkoxy compound, phosphorus and halogen; and the organoaluminum compound comprises organoaluminum I and organoaluminum II; wherein the solid catalyst component does not comprise a silica carrier, wherein the organoaluminum I has a general formula of AlR1R2R3, wherein R1, R2 and R3 are the same or different from each other and are independently C6 to C 20 wherein the organic aluminum II has the general formula AlR ' i R'2R'3, wherein R'1, R'2 and R'3 are the same as or different from each other and are each independently a C1-C5 hydrocarbon group.

[0013] The catalyst system of the present invention belongs to the Ziegler-Natta catalyst system used in ethylene polymerization.

[0014] In the present invention, "does not contain a silica carrier" means that the solid catalyst component does not contain a silica carrier intentionally added, but does not exclude trace amounts of silica present as impurities. Preferably, based on the weight of the solid catalyst component, silica is present in an amount of less than 0.5% by weight, more preferably, silica is present in an amount of less than 0.1% by weight, and most preferably, the solid catalyst component does not contain a silica carrier at all.

[0015] In some embodiments, in the organoaluminum I, R1, R2, and R3 are each independently C6 to C 20 Alkyl, preferably C6~C 20 of a straight chain alkyl group.

[0016] In some embodiments, in the organoaluminum I, R1, R2, and R3 are each independently C6 to C 12 Alkyl, preferably C6~C 10 The alkyl group is preferably a C6-C8 alkyl group.

[0017] In some embodiments, the organoaluminum I is selected from at least one of tri-n-hexylaluminum, tri-n-octylaluminum, tri-n-decylaluminum, tri-dodecylaluminum, tri-tetradecylaluminum, tri-hexadecylaluminum, tri-octadecylaluminum and tri-eicosylaluminum, more preferably tri-n-hexylaluminum and / or tri-n-octylaluminum.

[0018] In some embodiments, the organoaluminum II is selected from one or more of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum and triisobutylaluminum, more preferably triethylaluminum and / or triisobutylaluminum.

[0019] In some embodiments, the organoaluminum compound comprises one or more of tri-n-hexylaluminum, tri-n-octylaluminum, and tri-n-decylaluminum and one or more of trimethylaluminum, triethylaluminum, and triisobutylaluminum, preferably comprises one or more of tri-n-hexylaluminum and tri-n-octylaluminum and one or more of triethylaluminum and triisobutylaluminum, more preferably comprises tri-n-hexylaluminum and triethylaluminum, or comprises tri-n-octylaluminum and triethylaluminum.

[0020] In some embodiments, the molar ratio of the organoaluminum I to the organoaluminum II is (0.01-100):1, preferably (0.02-50):1, more preferably (0.1-10):1, more preferably (1-8):1, more preferably (3-6):1, and even more preferably (4-5):1.

[0021] In some embodiments, the molar ratio of total aluminum in the organoaluminum compound to titanium in the solid catalyst component is (5-5000):1, preferably (20-500):1, more preferably (100-400):1, and even more preferably (200-300):1.

[0022] In some embodiments, the catalyst system is prepared by mixing a solid catalyst component and an organoaluminum compound.

[0023] In some embodiments, based on the total weight of the solid catalyst component, the content of the titanium element is 1wt% to 15wt%, the content of the magnesium element is 10wt% to 30wt%, the content of the phosphorus element is 0.01wt% to 1wt%, the content of the alkoxy compound is 1wt% to 10wt%, and the content of the halogen is 40wt% to 70wt%.

[0024] In some embodiments, based on the total weight of the solid catalyst component, the content of the titanium element is 2wt% to 10wt%, the content of the magnesium element is 15wt% to 25wt%, the content of the phosphorus element is 0.1wt% to 0.8wt%, the content of the alkoxy compound is 2wt% to 8wt%, and the content of the halogen is 50wt% to 65wt%.

[0025] In some embodiments, the average particle size of the solid catalyst component is 2 to 10 microns, preferably 3 to 8 microns.

[0026] In some embodiments, the bulk density of the solid catalyst component is 0.3 to 0.5 g / ml, preferably 0.35 to 0.45 g / ml.

[0027] In the present invention, the average particle size of the solid catalyst component is measured by a Mastersizer 2000 instrument (Malvern, UK), and the bulk density of the solid catalyst component is measured according to ASTM D1895-96.

[0028] In some embodiments, the titanium element comes from a titanium compound, and the titanium compound can be various titanium compounds commonly used in the preparation of the solid component of the olefin polymerization catalyst. For example, the general formula of the titanium compound can be Ti(OR): a X b , where R is C1~C 14 Aliphatic hydrocarbon or C6~C 14 An aromatic hydrocarbon group, X is a halogen atom, a is an integer from 0 to 4, b is an integer from 0 to 4, and a+b=3 or a+b=4.

[0029] In some embodiments, preferably, the titanium compound is selected from at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, tetraethoxytitanium, triethoxytitanium monochloride, diethoxytitanium dichloride, triethoxytitanium trichloride, and titanium trichloride.

[0030] In some embodiments, the magnesium element comes from a magnesium compound, and the magnesium compound is selected from magnesium dihalide and a derivative of magnesium dihalide in which a halogen atom in the molecular formula is replaced by a hydrocarbon group or a halohydrocarbonoxy group, specifically including but not limited to magnesium chloride.

[0031] In some embodiments, the alkoxy compound is derived from an organic alcohol compound, and the organic alcohol compound is selected from a C1-C8 straight-chain alcohol or a branched alcohol, preferably at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-octanol, and isooctyl alcohol.

[0032] In some embodiments, the phosphorus element is derived from an organic phosphorus compound selected from a hydrocarbyl ester or a halogenated hydrocarbyl ester of orthophosphoric acid, or a hydrocarbyl ester or a halogenated hydrocarbyl ester of phosphorous acid.

[0033] In some embodiments, preferably, the organophosphorus compound is selected from trimethyl orthophosphate, triethyl orthophosphate, tributyl orthophosphate, triphenyl orthophosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, benzyl phosphite.

[0034] The solid catalyst component can be prepared using various methods known in the art.

[0035] In some embodiments, the method for preparing the solid catalyst component comprises:

[0036] dissolving a magnesium compound in a solvent system comprising at least one organic epoxy compound, at least one organic phosphorus compound, at least one organic alcohol compound, and at least one inert diluent;

[0037] adding a precipitation aid, then lowering the system temperature and adding a titanium compound to obtain a suspension system containing a solid component;

[0038] The system temperature is increased, and the suspension system is filtered, washed, and dried to obtain the solid catalyst component.

[0039] For example, the solid catalyst component of the present invention can be prepared with reference to CN112724284B or CN112724290B.

[0040] The present invention has no particular limitation on the number of times the titanium compound is added, which may be once, twice, three times, or more times; however, each time the titanium compound is added, it is added dropwise slowly.

[0041] In some embodiments, the organic epoxy compound is selected from at least one of an oxide of a C2-C8 aliphatic olefin or a diolefin, an oxide of a C2-C8 halogenated aliphatic olefin or a diolefin, a glycidyl ether, and an internal ether. Preferably, the organic epoxy compound is selected from ethylene oxide, propylene oxide, butylene oxide, butadiene oxide, butadiene dioxide, epichlorohydrin, methyl glycidyl ether, and diglycidyl ether.

[0042] In some embodiments, the inert diluent is selected from at least one of hexane, heptane, octane, decane, benzene, toluene, xylene, or derivatives thereof.

[0043] In some embodiments, the precipitation aid is selected from at least one of organic acids, organic anhydrides, organic ethers, and organic ketones, preferably at least one of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether, and pentyl ether.

[0044] The second aspect of the present invention provides an application of the above catalyst system in ethylene polymerization. Preferably, the second aspect of the present invention provides an application of the catalyst system of the present invention in ethylene polymerization to reduce the effect of temperature change on the molecular weight of ultra-high molecular weight polyethylene.

[0045] As known in the art, in the industrial production of ultra-high molecular weight polyethylene, the molecular weight of the ultra-high molecular weight polyethylene decreases with the increase of polymerization temperature, so the change of temperature will affect the molecular weight of the ultra-high molecular weight polyethylene. The catalyst system of the present application can reduce the influence of temperature on the molecular weight of the produced ultra-high molecular weight polyethylene and / or maintain the polymerization activity of the catalyst system for a long time. Reducing the influence of temperature on the molecular weight of the polymer product can make the molecular weight of the polyethylene polymer more stable, which is conducive to improving the quality of the ultra-high molecular weight polyethylene product.

[0046] In some embodiments, the catalyst system is suitable for slurry polymerization of ethylene, preferably for producing ultra-high molecular weight polyethylene under high temperature conditions of 70°C to 80°C.

[0047] In some embodiments, the solvent in the slurry polymerization of ethylene is selected from linear or branched alkanes, preferably hexane, heptane, octane, decane or derivatives thereof.

[0048] In some embodiments, the viscosity average molecular weight of the ultra-high molecular weight polyethylene is 4 million to 6 million.

[0049] In some embodiments, the polymerization temperature is 70 to 90°C, preferably 70 to 80°C.

[0050] In some embodiments, the polymerization reaction pressure is 0.05 to 10 MPa, preferably 0.1 to 5 MPa.

[0051] The third aspect of the present invention provides a method for preparing ultra-high molecular weight polyethylene, which comprises polymerizing ethylene in an inert solvent in the presence of the catalyst system of the present invention to produce ultra-high molecular weight polyethylene.

[0052] In some embodiments, the polymerization temperature is 70 to 90°C, preferably 70 to 80°C.

[0053] In some embodiments, the viscosity average molecular weight of the ultra-high molecular weight polyethylene may be 4 million to 6 million.

[0054] In some embodiments, the polymerization pressure may be 0.05 to 10 MPa, preferably 0.1 to 5 MPa.

[0055] In some embodiments, the inert solvent may be selected from linear or branched alkanes, preferably hexane, heptane, octane, decane or derivatives thereof.

[0056] The present invention has the following beneficial effects:

[0057] Compared with the catalyst system of the prior art, the catalyst system of the present invention is less sensitive to changes in polymerization temperature; that is, when the polymerization temperature changes, the change (calculated as a percentage) in the molecular weight of polyethylene, especially ultra-high molecular weight polyethylene, prepared using the catalyst system of the present invention is significantly less than the change in the molecular weight of polyethylene prepared using the catalyst system of the prior art. In addition, the catalyst system of the present invention can maintain polymerization activity for a long time; that is, the polymerization activity remains stable or substantially stable over time. Therefore, the catalyst system of the present invention can reduce the effect of temperature fluctuations on the molecular weight of the polymer during the polymerization process, and provide a polyethylene product with improved molecular weight uniformity.

[0058] Example

[0059] The following is a detailed description of the embodiments of the present invention. It should be understood that the embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0060] In the following embodiments:

[0061] The activity of the catalyst is expressed as the mass of ethylene converted to product per unit mass of catalyst, and the unit is kg polymer / g catalyst.

[0062] In the present invention, the viscosity average molecular weight (M η ) is measured by viscosity method according to standard GB / T1632.3-2010.

[0063] Preparation of solid catalyst components

[0064] 4.8 g of magnesium chloride, 55 ml of toluene, 3.0 ml of epichlorohydrin, 3.6 ml of tributyl phosphate and 7.6 ml of ethanol were added into a reactor, and the reaction was carried out for one hour at a stirring speed of 450 rpm and a temperature of 55°C. 0.8 g of phthalic anhydride was added, and the reaction was continued for one hour. The temperature was lowered to -10°C, 40 ml of titanium tetrachloride was added dropwise, and the temperature was gradually raised to 80°C. The temperature was kept constant for one hour, the mother liquor was filtered out, and the mixture was washed twice with 120 ml of toluene at 60°C, washed four times with an organic solvent hexane, and vacuum dried to obtain a solid catalyst component Z1.

[0065] 1.5 g of titanium tetrachloride, 4.0 g of magnesium chloride and 100 ml of tetrahydrofuran were added to a 250 ml three-necked flask, and the temperature was raised to 65°C under stirring. The reaction was kept at this temperature for 3 hours, and then the temperature was lowered to 35°C to be used as a mother liquor. 6 g of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1 micron) was added to another 250 ml three-necked flask, and the mother liquor after cooling was added. The temperature was kept at 35°C. After stirring for 1 hour, the mother liquor mixed with silica gel was spray dried by a spray dryer. The spraying conditions were: inlet temperature 195°C, outlet temperature 110°C, and a solid catalyst component Z2 was obtained.

[0066] Examples 1-15 and Comparative Examples 1-15, 25-34

[0067] In a 48-channel parallel pressure reactor (reaction volume 20 mL), the reactor was replaced with ethylene at room temperature, and organoaluminum I and organoaluminum II were added to the reactor. The temperature was maintained at a certain level, and the ethylene pressure was controlled at 0.3 MPa. Then, the solid catalyst component Z1 was added to the reactor and the polymerization reaction was carried out at a constant temperature for 2 hours.

[0068] Comparative Examples 16-24, 35-40

[0069] In a 48-channel parallel pressure reactor (reaction volume 20 mL), the reactor was replaced with ethylene at room temperature, and organoaluminum I and organoaluminum II were added to the reactor. The temperature was maintained at a certain level, and the ethylene pressure was controlled at 0.3 MPa. Then, the solid catalyst component Z2 was added to the reactor and the polymerization reaction was carried out at a constant temperature for 1 hour.

[0070] Examples 16-27 and Comparative Examples 41-46

[0071] In a 48-channel parallel pressure reactor (reaction volume 20 mL), the reactor is replaced with ethylene at room temperature, and organic aluminum I and organic aluminum II are added to the reactor. The temperature is maintained at a certain level, and the ethylene pressure is controlled to be 0.3 MPa. Then, the solid catalyst component Z1 is added to the reactor for a constant temperature polymerization reaction.

[0072] The polymerization activities and product properties of the above examples and comparative examples are shown in Tables 1-3 and Attached Figure 1 shown.

[0073] Table 1

[0074]

[0075]

[0076] Note 1: TEAL is triethylaluminum; TIBA is triisobutylaluminum;

[0077] THAL is tri-n-hexylaluminum;

[0078] TOAL is tri-n-octylaluminum; THDAL is tri-hexadecylaluminum.

[0079] Note 2: The molar ratio of aluminum element in the co-catalyst to titanium element in the solid catalyst component is n(A1) / n(Ti)=250.

[0080] From the experimental results, it can be found that when the long- and short-chain organoaluminum is used in combination (Examples 1-9), the polymerization temperature increases from 70°C to 80°C, and the viscosity-average molecular weight decreases by up to 22%; while the co-catalyst triethylaluminum or triisobutylaluminum system currently used in industry (Comparative Examples 1-6) has a viscosity-average molecular weight decrease of 50%. Comparing the use of long- and short-chain organoaluminum in combination with the use of long-chain organoaluminum alone (Comparative Examples 7-15), the viscosity-average molecular weight decreases slowly while maintaining a high polymerization activity, meeting the needs of industrial applications. For the silicon-containing catalyst system (Comparative Examples 16-24), the viscosity-average molecular weight decreases more in the long- and short-chain organoaluminum combination and the long-chain organoaluminum system than in the short-chain organoaluminum system, indicating that the effect of organoaluminum on the viscosity-average molecular weight against temperature fluctuations is related to the catalyst system.

[0081] Table 2

[0082]

[0083]

[0084] Note 3: Polymerization temperature 80℃.

[0085] From the experimental results, it can be found that when the long- and short-chain organoaluminum is used in combination (Examples 10-15), the aluminum-titanium ratio is increased from 100 to 350, and the viscosity-average molecular weight decreases by up to 7%; while the co-catalyst triethylaluminum or triisobutylaluminum system currently used in industry (Comparative Examples 25-28) has a viscosity-average molecular weight decrease of 24%. Comparing the use of long- and short-chain organoaluminum in combination with the use of long-chain organoaluminum alone (Comparative Examples 29-34), the viscosity-average molecular weight decreases slowly while maintaining a high polymerization activity, meeting the needs of industrial applications. For the silicon-containing catalyst system (Comparative Examples 35-40), the viscosity-average molecular weight decrease of the long- and short-chain organoaluminum combination is higher than that of the long-chain organoaluminum and short-chain organoaluminum systems, indicating that the effect of organoaluminum on the viscosity-average molecular weight against the fluctuation of the aluminum-titanium ratio is related to the catalyst system.

[0086] Table 3

[0087]

[0088]

[0089] Note 4: The molar ratio of aluminum in the co-catalyst to titanium in the solid catalyst component is n(A1) / n(Ti) = 250; the polymerization temperature is 80°C.

[0090] From the experimental results, it can be found that the activity of the long-chain and short-chain organoaluminum composites (Examples 16-27) remains stable as the polymerization time increases; the activity of the long-chain organoaluminum system also remains stable, but the overall activity is too low (Comparative Examples 41-43). The activity of the co-catalyst triethylaluminum system currently used in industry (Comparative Examples 44-46) gradually decreases as the polymerization time increases.

[0091] Therefore, the polymerization system using a combination of long- and short-chain organic aluminum has better temperature stability, aluminum-titanium ratio stability and longer polymerization life.

[0092] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0093] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A catalyst system, characterized in that The catalyst system comprises a solid catalyst component and an organoaluminum compound; the solid catalyst component comprises titanium, magnesium, an alkoxy compound, phosphorus and a halogen; and the organoaluminum compound comprises organoaluminum I and organoaluminum II; wherein the solid catalyst component does not contain a silica carrier; The organic aluminum I has the general formula AlR1R2R3, wherein R1, R2 and R3 are the same or different from each other and are independently C6 to C 20 and wherein the organoaluminum II has the general formula A1R'1R'2R'3, wherein R'1, R'2 and R'3 are the same or different from each other and are each independently a C1 to C5 hydrocarbon group.

2. The catalyst system according to claim 1, characterized in that In the organic aluminum I, R1, R2 and R3 are each independently C6 to C 20 The alkyl group is preferably C6~C 20 Preferably, the organoaluminum I is selected from at least one of tri-n-hexyl aluminum, tri-n-octyl aluminum, tri-n-decyl aluminum, tri-dodecyl aluminum, tri-tetradecyl aluminum, tri-hexadecyl aluminum, tri-octadecyl aluminum and tri-eicosyl aluminum; More preferably, R1, R2 and R3 are each independently C6 to C 12 Alkyl, more preferably C6~C 10 The alkyl group is more preferably a C6-C8 alkyl group.

3. The catalyst system according to claim 1 or 2, characterized in that The organoaluminum II is selected from one or more of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum and triisobutylaluminum.

4. The catalyst system according to any one of claims 1 to 3, characterized in that The molar ratio of the organoaluminum I to the organoaluminum II is (0.01-100):1, preferably (0.02-50):1, and more preferably (0.1-10):

1.

5. The catalyst system according to any one of claims 1 to 4, characterized in that The molar ratio of the total aluminum in the organic aluminum compound to the titanium in the solid catalyst component is (5-5000):1, preferably (20-500):

1.

6. The catalyst system according to any one of claims 1 to 5, characterized in that Based on the total weight of the solid catalyst component, the content of the titanium element is 1wt% to 15wt%, the content of the magnesium element is 10wt% to 30wt%, the content of the phosphorus element is 0.01wt% to 1wt%, the content of the alkoxy compound is 1vwt% to 10wt%, and the content of the halogen is 40wt% to 70wt%; Preferably, based on the total weight of the solid catalyst component, the content of the titanium element is 2wt% to 10wt%, the content of the magnesium element is 15wt% to 25wt%, the content of the phosphorus element is 0.1wt% to 0.8wt%, the content of the alkoxy compound is 2wt% to 8wt%, and the content of the halogen is 50wt% to 65wt%.

7. The catalyst system according to any one of claims 1 to 6, characterized in that The average particle size of the solid catalyst component is 2 to 10 microns, preferably 3 to 8 microns; And / or, the bulk density of the solid catalyst component is 0.3 to 0.5 g / ml, preferably 0.35 to 0.45 g / ml.

8. The catalyst system according to any one of claims 1 to 7, characterized in that The titanium element comes from a titanium compound, and the general formula of the titanium compound is Ti(OR) a X b , where R is C1~C 14 Aliphatic hydrocarbon or C6~C 14 An aromatic hydrocarbon group, X is a halogen atom, a is an integer from 0 to 4, b is an integer from 0 to 4, and a+b=3 or 4; preferably, the titanium compound is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, tetraethoxytitanium, monochlorotriethoxytitanium, dichlorodiethoxytitanium, trichloromonoethoxytitanium, and titanium trichloride; And / or, the magnesium element is derived from a magnesium compound, wherein the magnesium compound is selected from at least one of magnesium dihalide and a derivative of magnesium dihalide in which a halogen atom in the molecular formula is replaced by a hydrocarbon group or a halohydrocarbonoxy group, preferably magnesium chloride; And / or, the alkoxy compound is derived from an organic alcohol compound, the organic alcohol compound is selected from a C1-C8 straight-chain alcohol or a branched-chain alcohol, preferably at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-octanol, and isooctyl alcohol; And / or, the phosphorus element comes from an organic phosphorus compound, and the organic phosphorus compound is selected from a hydrocarbon ester or a halogenated hydrocarbon ester of orthophosphoric acid, a hydrocarbon ester or a halogenated hydrocarbon ester of phosphorous acid; preferably, the organic phosphorus compound is selected from trimethyl orthophosphate, triethyl orthophosphate, tributyl orthophosphate, triphenyl orthophosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite and benzyl phosphite.

9. The catalyst system according to any one of claims 1 to 8, characterized in that The preparation method of the solid catalyst component comprises: dissolving a magnesium compound in a solvent system comprising at least one organic epoxy compound, at least one organic phosphorus compound, at least one organic alcohol compound, and at least one inert diluent; adding a precipitation aid, then lowering the system temperature and adding a titanium compound to obtain a suspension system containing a solid component; The system temperature is increased, and the suspension system is filtered, washed, and dried to obtain the solid catalyst component.

10. The catalyst system according to claim 9, characterized in that The organic epoxy compound is selected from at least one of oxides of C2-C8 aliphatic olefins or dienes, oxides of C2-C8 halogenated aliphatic olefins or dienes, glycidyl ethers and internal ethers; preferably, the organic epoxy compound is selected from ethylene oxide, propylene oxide, butylene oxide, butadiene oxide, butadiene dioxide, epichlorohydrin, methyl glycidyl ether and diglycidyl ether; and / or, the inert diluent is selected from at least one of hexane, heptane, octane, decane, benzene, toluene, xylene, or derivatives thereof; And / or, the precipitation aid is selected from at least one of organic acids, organic anhydrides, organic ethers, and organic ketones, preferably at least one of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether, and pentyl ether.

11. Use of the catalyst system according to any one of claims 1 to 10 in ethylene polymerization, preferably in ethylene polymerization to reduce the effect of temperature change on the molecular weight of ultra-high molecular weight polyethylene.

12. The use according to claim 11, characterized in that: The catalyst system is used for slurry polymerization of ethylene, preferably for slurry polymerization of ultra-high molecular weight polyethylene at 70°C to 90°C.

13. The use according to claim 12, characterized in that: The solvent in the slurry polymerization reaction is selected from linear or branched alkanes, preferably hexane, heptane, octane, decane or their derivatives; And / or, the viscosity average molecular weight of the ultra-high molecular weight polyethylene is 4 million to 6 million; and / or, the polymerization temperature is 70 to 90° C., preferably 70 to 80° C.; And / or, the polymerization reaction pressure is 0.05 to 10 MPa, preferably 0.1 to 5 MPa.

14. A method for preparing ultra-high molecular weight polyethylene, characterized in that: The preparation method comprises polymerizing ethylene in an inert solvent in the presence of the catalyst system described in any one of claims 1 to 10 to produce ultra-high molecular weight polyethylene.

15. The preparation method according to claim 14, characterized in that: The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 4 million to 6 million; and / or, the polymerization temperature is 70 to 90°C, preferably 70 to 80°C and / or, the polymerization reaction pressure is 0.05 to 10 MPa, preferably 0.1 to 5 MPa; And / or, the inert solvent is selected from linear or branched alkanes, preferably hexane, heptane, octane, decane or derivatives thereof.

Citation Information

Patent Citations

  • Method for preparing superhigh molecular weight polythene catalyst and application thereof

    CN101235109A

  • Composite supported catalyst used for synthesizing ultrahigh molecular weight polyethylene and preparation method thereof

    CN103509141A

  • Catalyst component used for ethylene homopolymerization or copolymerization reaction, and catalyst thereof

    CN105566523A

  • Catalyst component for ethylene polymerization reaction, catalyst, and preparation method of catalyst component

    CN105622802A

  • Internal electron donor of ethylene polymerization Ziegler-Natta catalyst, catalyst component and preparation method

    CN107556409A